Hydrogen peroxide photoformation in particulate matter and its contribution to S(IV) oxidation during winter in Fairbanks, Alaska - M. O. Sunday; M. O. Sunday; L. M. Dahler Heinlein; J. He; A. Moon; S. Kapur; T. Fang; T. Fang; K. C. Edwards; F. Guo; F. Guo; J. Dibb; et al. (Atmospheric Chemistry and Physics)
The high levels of sulfate in wintertime particles in Fairbanks, Alaska, are a subject of keen research interest and regulatory concern. Recent results from the 2022 Alaska Layered Pollution And Chemical Analysis (ALPACA) field campaign indicate that roughly 40 % of wintertime sulfate in Fairbanks is secondary, with hydrogen peroxide (HOOH) the dominant oxidant. Since formation of HOOH in the gas phase should be negligible during ALPACA because of high levels of NOx, we examined whether reactions within particles could be a significant source of HOOH. To test this, we collected particulate matter (PM) samples during the ALPACA campaign, extracted them, illuminated them with simulated sunlight, and measured HOOH production. Aqueous extracts showed significant light absorption, a result of brown carbon (BrC) from sources such as residential wood combustion. Photoformation rates of HOOH in the PM extracts (PMEs; normalized to Fairbanks winter sunlight) range from 6 to 71 µM h−1. While light absorption is nearly independent of pH, HOOH formation rates decrease with increasing pH. Extrapolating to the concentrated conditions of aerosol liquid water (ALW) gives an average rate of in-particle HOOH formation of ∼ 0.1 M h−1. Corresponding rates of sulfate formation from particle-produced HOOH are 0.05–0.5 µg<mspace linebreak="nobreak" width="0.125em"/>m-3<mspace linebreak="nobreak" width="0.125em"/>h-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="53pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="bbefb9113aea0e66c18f7309e2e62feb"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-5087-2025-ie00001.svg" width="53pt" height="15pt" src="acp-25-5087-2025-ie00001.png"/></svg:svg>, accounting for a significant portion of the secondary sulfate production rate. Our results show that HOOH formed in particles makes an important contribution to sulfate formation in ambient wintertime particles, even under the low actinic flux conditions typical of winter in subarctic locations like Fairbanks.